Disqualification of arbitrator - Idris, Izzat (2011)
In Arbitration, an arbitrator has important role to conduct the Arbitration proceeding according to the Act. It is only natural for courts faced with enforcement of an award from a reputed institutional arbitration to be more accommodating, considering the institution’s reputation is running a well administered and supervised arbitration. According to the Arbitration Act 2005, an arbitrator can be disqualifying due to some circumstances. This section is set out because of to give opportunity to the parties have fairness in the arbitration. Therefore, the objective of this study is to identify the legal problem in disqualifying the arbitrator. The methodologies of this study have been separated into few steps; identifying the research issue, literature review, data collection, research analysis, and conclusion and recommendation. This approach is to ensure that the collection of the information and the data analyzing can be precisely implemented. An investigation of the most frequent reasons for disqualifying an arbitrator by Court according to the Arbitration Act is done to create awareness among the arbitrator. So the parties have equal trust in arbitration proceeding. It is found out that the factor of disqualifying and arbitrator is impartiality, independence, duty to disclose, misconduct, qualification and bias. In addition, the court are using tests in order to identify an arbitrator is disqualifying. Conclude that, from the result of the analysis there are cases reported under the Malaysia law journal which the disqualifying an arbitrator according to arbitration proceeding. Under the Arbitration Act 2005, the disputes party can send the notice to the tribunal or Court if they feel that arbitrator not having fairness in the proceeding in fifteen days.